The Future Prospect of Mobile Banking Technology Enhancement in Indonesia - Noerlina Noerlina; Djak Cindy Freda; Glen Mayo; Yehezkiel Kevin Tirtawijaya; Josephine Samuel (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2023)
FinTech is a brand-new industry for the banking and finance sectors. Its fundamental concept is to use information-technology-based solutions to improve efficiency in financial markets and banking transactions for consumers, banks, enterprises, and other ecosystem members. FinTech represents a system-level transformation in the financial services industry that has resulted in the creation of new actors and the convergence of capabilities. Electronic financial transfers via online banking and mobile payment have grown in popularity as the Internet and cell phones have evolved. The shift from traditional cash to digital money has blurred the distinction between data and money. In this paper, we reviewed the literature on fintech between 2018 and 2021. We discussed the state of the fintech ecosystem and mobile banking technology at the moment. The research context for this study is the development of financial technology (FinTech). The Fintech industry’s great potential and expansion in Indonesia must be backed up by a solid legal framework in the shape of Indonesian law and the law should be able to reach and incorporate all forms of fintech services.